The Role Of Training In Mediating The Effect Of Competence, Compensation On Employee Performance - Ivalaina Astarina; Tomy Fitrio; Angga Hapsila; Agus Supriyadi; Dwi Cahyono (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2022)
AbstractThis study aimed to develop a conceptual model of the relationship between competence, compensation, and employee performance hammering training on the performance of employees of public health centres in Indragiri Hulu Regency, Riau Province. Data analysis was carried out using Structural Equation Model (SEM) Smart PLS. The main findings in this study are competency and compensation which affect the employee performance. Training plays a role in mediating the effect of competence and compensation on employee performance. The acceptance of the hypothesis that claimed the role of mediation from training shows the importance of training as one of the strategies in improving employee performance.Keywords:Employee performance, training, competence, compensationPeran Pelatihan dalam Memediasi Pengaruh Kompetensi, Kompensasi terhadap Kinerja Karyawan AbstrakTujuan dari penelitian ini adalah untuk mengembangkan model konseptual hubungan antara kompetensi, kompensasi dan kinerja pegawai dengan menawarkan solusi diklat sebagai variabel mediasi yang menjembatani hubungan kompetensi dan kompensasi terhadap kinerja pegawai puskesmas di Kabupaten Indragiri Hulu Propinsi Riau. Sampel pada penelitian ini adalah 127 orang pegawai puskesmas di Kabupaten Indragiri Hulu. Teknik analisa data menggunakan Structrual Equation Model (SEM) Smart PLS. Temuan utama pada penelitian ini adalah kompetensi dan kompensasi berpengaruh terhadap kinerja pegawai. Diklat berperan dalam memediasi pengaruh kompetensi dan kompensasi terhadap kinerja pegawai. Diterimanya hipotesis yang menyatakan peran mediasi dari diklat memperlihatkan pentingnya diklat sebagai salah satu strategi dalam meningkatkan kinerja pegawai.Kata kunci:Kinerja pegawai, diklat, kompetensi, kompensasi